2018
DOI: 10.1109/tnsre.2018.2868486
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method of Emergency Situation Detection for a Brain-Controlled Vehicle by Combining EEG Signals With Surrounding Information

Abstract: In this paper, to address the safety of brain-controlled vehicles under emergency situations, we propose a novel method of emergency situation detection by fusing driver electroencephalography (EEG) signals with surrounding information. We first build a novel EEG-based detection model of driver emergency braking intention. We then recognize emergency situations by fusing the result of the proposed EEG-based intention detection model with that of the obstacle detection model based on surrounding information. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 20 publications
0
41
0
Order By: Relevance
“…Despite these challenges, several studies have demonstrated the feasibility of BCVs. We can mention, for instance, control of a vehicle in four main directions [107], [108], methods for obstacle avoidance [109], [110], and hand brake assistance in emergency situations [111], [112], using diverse platforms such as vehicle simulators, virtual reality vehicles, vehicles in video games, quadcopters, drones, helicopters, and fixed-wings aircrafts. A general simulator-based procedure for training a participant is shown in Fig.…”
Section: A State-of-the-artmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these challenges, several studies have demonstrated the feasibility of BCVs. We can mention, for instance, control of a vehicle in four main directions [107], [108], methods for obstacle avoidance [109], [110], and hand brake assistance in emergency situations [111], [112], using diverse platforms such as vehicle simulators, virtual reality vehicles, vehicles in video games, quadcopters, drones, helicopters, and fixed-wings aircrafts. A general simulator-based procedure for training a participant is shown in Fig.…”
Section: A State-of-the-artmentioning
confidence: 99%
“…In a series of studies by Bi et al [111], [117]- [121], different approaches to identify and predict the driver's intention for Arguably, the major limitation on BCVs is the availability of more informative neural signals than those that EEG or EMG can provide. The use of noninvasive brain signals has led to significant contributions, in particular, better braking systems, but a comprehensive control of a vehicle requires fine-tuned actions.…”
Section: A State-of-the-artmentioning
confidence: 99%
“…The fMRI is usually employed as a hybrid method with the EEG to obtain significant results in real-time systems. [12], [13].…”
Section: ) Fmrimentioning
confidence: 99%
“…EEG data helps to assess the states of the brain and hence EEG signals are commonly used in real-world applications [25,26]. In the EEG-based brain-computer interface (BCI) design, well-recorded data are difficult to collect because most of the subjects are affected by interior and exterior disturbances.…”
Section: Eeg Experimentsmentioning
confidence: 99%